2009
DOI: 10.1016/j.ijrobp.2008.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Using Fluorodeoxyglucose Positron Emission Tomography to Assess Tumor Volume During Radiotherapy for Non–Small-Cell Lung Cancer and Its Potential Impact on Adaptive Dose Escalation and Normal Tissue Sparing

Abstract: Purpose Fluorodeoxyglucose–positron emission tomography (FDG-PET) has improved target definition in non-small cell lung cancer (NSCLC), but few data exist regarding changes during radiotherapy. The purpose of this study was to quantify changes in FDG-avid tumor volume and examine its potential use in adaptive radiotherapy for tumor dose escalation or normal tissue sparing. Methods and Materials As part of a pilot study, fourteen patients with stage I-III NSCLC underwent FDG-PET-CT prior to radiation (RT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 26 publications
4
92
0
Order By: Relevance
“…The outcome for patients with NSCLC remains quite poor despite improvements in radiotherapy and chemotherapy in the past decade [2]. Tumor-node-metastasis (TNM) stage is currently the most important prognostic factor for survival in NSCLC, in which stage IV is the most advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome for patients with NSCLC remains quite poor despite improvements in radiotherapy and chemotherapy in the past decade [2]. Tumor-node-metastasis (TNM) stage is currently the most important prognostic factor for survival in NSCLC, in which stage IV is the most advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this imaging modality is increasingly used for response assessment in lung cancer. Several reports have documented changes in 18 F-FDG uptake pattern in response to external-beam radiotherapy (16,17), chemotherapy (18), or biologic agents (19). Building on these reports, it was the aim of the current study to investigate the utility of 18 F-FDG PET/CT for response assessment in RFA-treated lung lesions and for the detection and prediction of local recurrence.…”
mentioning
confidence: 99%
“…We found that compared to nonadaptive planning, adaptive planning significantly reduced radiation dose to OARs (lungs, cord, esophagus, and chest wall) for these studied patients. Given the hypofractionated nature of lung SBRT, even small dose reductions to OARs could lead to significant reduction in normal tissue complication probability (NTCP) 13 .…”
Section: Interpretation Of Resultsmentioning
confidence: 99%